Resistance of Local Actors to the Leasing of Water Supply in the Village of Atchannou in South-West Benin - TOGBE, Codjo Timothée; KOUKPOSSI, Albert Omolegbé (Advances in Social Sciences Research Journal, 2022)
Leasing as an innovation in the governance of the Village Water Supply System (VWSS) should, a priori, allow local authorities to manage the delivery of drinking water to rural populations in Benin rationally and transparently. However, instead of being favourably welcomed, this system has met with resistance from local actors. Based on the premise that leasing involves issues that are insufficiently elucidated by its innovators, this article analyses the causes of the resistance observed in its implementation. To achieve this goal, a qualitative social science research method was used, favouring discussion with 18 participants. The data were analysed in the backdrop of the market mode of local governance and fuzzy set theory. The results of this research show that the populations of Atchannou Village do not fully accept the leasing of water, or at least they set out the preconditions to be met by the local government authorities before this innovative approach to governance of the water point can become operational: guaranteeing the management of the funds from the sale of water (1), and repaying the debts related to the community management of the water supply (2). The local actors are therefore in a logic of preserving the interests that will be generated by the sale of water, which is now retroceded to the Municipality; this further increase their resistance to the leasing of the water supply system.